Chemisorption and Physisorption at the Metal/Organic Interface: Bond Energies of Naphthalene and Azulene on Coinage Metal Surfaces - Kachel, Stefan R.; Klein, Benedikt P.; Morbec, Juliana M.; Schöniger, Maik; Hutter, Mark; Schmid, Martin; Kratzer, Peter; Meyer, Bernd; Tonner, Ralf; Michael Gottfried, J. (Journal of Physical Chemistry C, 2020)
Organic/inorganic hybrid interfaces play a prominent role in organic (opto)electronics, heterogeneous catalysis, sensors, and other current fields of technology. The performance of the related devices and processes depends critically on the nature and strength of interfacial interaction. Here, we use the molecular isomers naphthalene (Nt) and azulene (Az) on the Ag(111) and Cu(111) surfaces as model systems that cover different bonding regimes from physisorption to chemisorption. Az also serves as a model for nonalternant molecular electronic materials and for topological 5-7 defects in graphene. The interaction energies are determined from the quantitative analysis of temperature-programmed desorption data. On both surfaces, Az binds more strongly than Nt, with zero-coverage desorption energies (in kJ/mol) of 120 for Az/Ag and 179 for Az/Cu, compared to 103 for Nt/Ag and 114 for Nt/Cu. The integrated experimental energies are compared with adsorption energies from density-functional theory (DFT) calculations, which include van der Waals contributions using four different correction schemes for the PBE functional: (1) the DFT-D3 scheme with Becke-Johnson damping, (2) the vdWsurf correction based on DFT-TS, (3) a many-body dispersion correction scheme, and (4) the D3surf scheme. Differences in the performance of these methods are discussed. Periodic energy decomposition analysis reveals details of the surface chemical bond and confirms that Az/Cu forms a chemisorptive bond, while the other systems are physisorbed. The variation of the adsorbate-substrate interaction with the topology of the Ï€-electron system and the type of surface can be employed to modify the interface properties in graphene-based and organic electronic devices.
CRIS-Team Scopus Importer:2020-04-14